2023
DOI: 10.1108/maj-10-2022-3734
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carbon emissions on audit fees

Jianhua Tan,
Kam C. Chan,
Samuel Chang
et al.

Abstract: Purpose This paper aims to examine the effect of carbon emissions on audit fees. The authors hypothesize that firms in cities with higher carbon emission levels have lower reporting transparency, higher return volatility or are subject to higher reputation risk, causing them to be charged higher audit fees for auditing services. Design/methodology/approach The authors use panel data of 25,960 firm-year observations from a sample of Chinese firms. The carbon emission data for each Chinese city are obtained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…However, Du et al (2018) found that auditors applauded environmentally friendly enterprises, thereby charging lower audit fees [ 67 ]; the relationship should be negative. A possible reason for the mixed conclusions was that previous studies focused on only the command-and-control environmental regulation [ 18 , 19 , 21 ] or the market-based incentive environmental regulation [ 20 , 24 ], which were defective and might be regarded as a good opportunity by some enterprises but treated as a significant burden by some other enterprises. Therefore, it is worthy of in-depth exploration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, Du et al (2018) found that auditors applauded environmentally friendly enterprises, thereby charging lower audit fees [ 67 ]; the relationship should be negative. A possible reason for the mixed conclusions was that previous studies focused on only the command-and-control environmental regulation [ 18 , 19 , 21 ] or the market-based incentive environmental regulation [ 20 , 24 ], which were defective and might be regarded as a good opportunity by some enterprises but treated as a significant burden by some other enterprises. Therefore, it is worthy of in-depth exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Second, in terms of research interpretation, some researchers have explored the reaction of auditors to the environmental events or environmental risks; however, the existing research on how environmental regulation affects audit fees can still be broadly categorised into the ‘audit cost effect’ and the ‘risk compensation effect’ from the traditional perspective [ 20 , 24 ]. Nonetheless, related environmental channels are largely neglected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations